KAJIAN TANAH ENDAPAN PERAIRAN SEBAGAI MEDIA TANAM PERTANIAN KOTA - Haryanta, Dwi; Thohiron, Mochammad; Gunawan, Bambang (Journal of Research and Technology, 2017)
Siltation of the river, ditches, reservoirs in urban areas is a problem because it causes flooding. The government annually undertakes dredging of the precipitate for the flow of water to flow smoothly. Soil sedimentary water potential to be utilized as a medium of planting in the development of urban agriculture. The research was conducted by survey method in Surabaya city waters. The sample was taken using random method of choosing, that is choosing condition of place environment and soil condition which is possible for planting medium. Soil sediment samples were observed for pH, color, structure, texture, organic matter content, Nitrogen (N-total), K2O and P2O5. The result of this research shows that all of the textured sedimentary soil content of clay is 89,87- 92,14%, organic material content is about 5,96-7,60%, total N-content is 0,09-0,13%, K2O content between 0,88-1,12%, and P2O5 content between 2,08-2,44%. The color of soil was grayish-black-black. The mud deposits of the housing sewer are the most crumbling and the most consumptive reservoir are sludge. Sewage soil sludge is potentially used as a planting medium in the development of urban agriculture.